Halo Effect in Subjective Performance Evaluation Bias - Andi Ina Yustina; Gudono Gudono (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study aimed not only to examine the effect of the objective measure and controllability on subjective performance evaluation but also to prove empirically the halo effect phenomenon which is present in the evaluation process when evaluators are faced with two or more different measurement dimensions. This study used a 2x2 factorial web-based experiment involving 62 undergraduate students and 77 sales managers in the Telecommunications industry. The results reveal the subjective performance evaluation manager is directly influenced by objective measurement based on sales performance. Subjective evaluation of performance evaluator will be high when the objective performance information managers showed a high score and vice versa. The level of controllability affects undergraduate students in conducting subjective performance rating. This evidence suggests that the two subjects of this research using their discretion in conducting the performance appraisal rating. Halo effect is proven to have high correlation with two different dimensions of performance measurement.